The design and evaluation of ciprofloxacin-loaded nanoformulations using Ipomoea batatas starch nanoparticles - Tolulope O. Ajala; Omobolanle A. Omoteso; Oladotun M. Awe (SpringerOpen, 2023)
Abstract Background Starch nanoparticle derivatives are gaining popularity as drug delivery vehicles because of their biocompatibility, better mechanical characteristics, heat stability properties, impediment qualities, permeability capabilities, and flexibility to be changed for specific predetermined functions. The effect of techniques and processing time on the physiochemical and drug release characteristics of sweet potato (Ipomoea batatas) starch nanoparticles and their ciprofloxacin-loaded nanoformulations was studied. Results Scanning electron microscopy confirmed that the treated starch formed nanoparticles and also revealed significant changes in the morphology of the treated starches. The water absorption capacity of chemically treated starch nanoparticles (CTSN)-3 days was the highest, whereas CTSN-6 days had the maximum solubility. The functional groups present in the starch nanoparticles were confirmed by Fourier transform infrared spectroscopy and Raman. The thermal characteristics of starch nanoparticles were established using hot-stage microscopy, differential scanning calorimetry, and thermogravimetric analysis. The percentage drug content and loading efficiency of the model drug were extensively boosted by the chemical and mechanical treatment of Ipomoea batatas starch. In comparison with the untreated potato starch (UPS), release times for loaded drug were significantly longer for the chemically treated starch nanoparticles and mechanically treated starch nanoparticles (MTSN) starches in the rank order of T 80%, CTSN-3 days > MTSN-3 days > CTSN-6 days > MTSN-6 days > UPS. The main kinetics of drug release were Fickian diffusion. Conclusion After 3 days of acid hydrolysis, sweet potato starch yielded nanoparticulate carriers that can be employed for controlled or extended release of medicines that are poorly water soluble.